BIOSINTESIS ASAM LEMAK OMEGA-3 DARI PALM OIL MILL EFFLUENT (POME) MELALUI PROSES ANAEROBIK DENGAN MIKROAERASI - Indira Salsabilla Ayuwibowo; Annisa Karunia; Hanifrahmawan Sudibyo; Wiratni Budhijanto (Universitas Muhammadiyah Jakarta, 2018)
Palm oil is one of Indonesia's leading export commodities. By 2020, the target of crude palm oil (CPO) production in Indonesia is 30 million tons. It is predicted that such production target is accompanied by a consequence of palm oil mill effluent (POME) emission as waste water, which will reach 90 million tons of POME waste per year. POME has high organic content which are characterized as chemical oxygen demand (COD) values, which ranges from 50,000 - 200,000 mg / L and pH values ranges from 4-4.5. Untreated POME is a serious environmental problem and therefore POME processing is urgently needed. One of the ideas is converting POME into more valuable products, by biosynthesis of omega-3 fatty acids from POME with anaerobic processes. The common product collected from anaerobic digestion is biogas. This study, however, intended to stop the process in the intermediate product, which is a series of organic acids, without biogas formation. The study aimed to explore the effect of controlled air injection in anaerobic processes on acid productions as the intermediate product in anaerobic digestion. The result showed that limited air injection (microaeration) improved process performance, especially with respect to acid production. Whereas through GC-FID analysis, the profile of saturated and unsaturated fatty acids was obtained. The acids have the potential to produce omega-3 fatty acids such as the appearance of nervoic, cis-eicosadienoic, cis-eicosapentanoic, and linolenic acids, with the peak of appearance occurring at different process durations. This preliminary study indicated that the biosynthesis of omega-3 fatty acids from POME through the anaerobic process was possible to be carried out but further study would be needed for process optimization.